Experiment and numerical modeling of stratified downdraft gasification using rice husk and wood pellet - Kittipass Wasinarom; Jarruwat Charoensuk (My University, 2019)
Stratified downdraft gasification using rice husks and wood pellets was carried out under different air mass flow rates using both experimental and numerical methods. The flame propagation rate was calculated from the temperature profile at different time steps and was used as the prerequisite to calculate the equivalent ratio in modeling the combustion zone. Chemical equilibrium modeling was employed to predict the temperature and composition of the sample in the combustion zone. Finite kinetic modeling was used to simulate the reduction zone. The initial temperature and composition of the reduction zone simulation were obtained from the chemical equilibrium results taken from the combustion zone. The flame propagation speed of the rice husk was found to be around five times greater than wood pellet at the same air flow rate. The peak temperature of both fuels had similar values. For all air mass flow rates, the equilibrium modeling over-estimated the peaks in comparison with the experimental tests. The kinetic model was sensitive to the input temperature at the zone inlet. The predicted temperature in the reduction zone demonstrated high kinetic activity at the top of the zone due to a high gas temperature. The predicted temperature was in agreement with the experimental test results.
Keywords: Husk; Pellet; Mass flow rate; Thermochemical Biomass Conversion Processes